2012
DOI: 10.1186/1758-3284-4-19
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic therapy in the management of metastatic or advanced salivary gland cancers

Abstract: Salivary gland cancers are very rare tumors. They are characterized by a histologic heterogeneity and a poor outcome. According to this rarity, few prospective data are available to date. No standard recommendations could be held for the use of systemic therapy in these tumors. Several case reports and small studies have investigated the contribution of different agents of chemotherapy. With the extension of molecular biology approach in oncology several signaling pathways have been discovered in different can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 87 publications
1
80
1
5
Order By: Relevance
“…Additionally, Meredith et al reported that SDC was not sensitive to chemotherapy (9). Therefore, treatment efficacy remains unclear, and there is currently no consensus regarding chemotherapy for SDC (19,31,32).…”
Section: Sdc Was First Described In 1968 Bymentioning
confidence: 99%
“…Additionally, Meredith et al reported that SDC was not sensitive to chemotherapy (9). Therefore, treatment efficacy remains unclear, and there is currently no consensus regarding chemotherapy for SDC (19,31,32).…”
Section: Sdc Was First Described In 1968 Bymentioning
confidence: 99%
“…[3][4][5] Lung metastasis and nerve metastasis are the biological characteristics of SACC. [6][7][8] It has been reported that the incidence of SACC with distant metastasis ranged from 35 to 50% of all cases. Lung was the most common organ of its distant metastasis, and lung metastasis is still the leading death cause of patients with SACC.…”
mentioning
confidence: 99%
“…4,5 Although the 5-year survival rate is high for patients with SACC, probably because of the slow growth of the tumor, the 10-and 15-year prognoses are poor because of the frequent local recurrences and distant metastases. [6][7][8] Although multiple genetic and epigenetic alterations have been detected in SACC, 3,9-13 the precise molecular mechanisms of progression and metastasis of SACC remain unknown.MicroRNAs (miRNAs) are small non-coding RNA molecules, with a length of 20-22 nucleotides, that regulate gene expression by either translational inhibition or mRNA degradation. miRNAs function as either oncogenes or tumor suppressors by inhibiting the expression of target genes, some of which are either directly or indirectly involved with canonical signaling pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The biological properties of SACC include slow local growth, high incidences of nerve and blood vessel invasion, infrequent regional metastases and frequent local recurrence, poor long-term prognosis and relatively indolent distant metastases. [3][4][5][6] Surgical resection is still the primary method for treating SACC, and postoperative radiotherapy is necessary to kill remaining cancer cells and prevent distant metastases. 5,6 Despite recent advances in surgery and adjuvant therapy, the overall 10-year survival and incidence of tumour recurrence in SACC patients have not significantly improved.…”
Section: Introductionmentioning
confidence: 99%